Long-Term Proton Pump Inhibitor Therapy and Falls and Fractures in Elderly Women: A Prospective Cohort Study - Lewis, J.R.; Barre, D.; Zhu, K.; Lim, E.; Hughes, Jeffrey David; Prince, R. (American Society for Bone and Mineral Research, 2014)
Proton pump inhibitors (PPIs) are widely used in the elderly. Recent studies have suggested that long-term PPI therapy is associated with fractures in the elderly, however the mechanism remains unknown. We investigated the association between long-term PPI therapy ≥1 year and fracture risk factors including bone structure, falls, and balance-related function in a post hoc analysis of a longitudinal population-based prospective cohort of elderly postmenopausal women and replicated the findings in a second prospective study of falling in elderly postmenopausal women. Long-term PPI therapy was associated with increased risk of falls and fracture-related hospitalizations; adjusted odds ratio (AOR) 2.17; 95% CI, 1.25–3.77; p = 0.006 and 1.95; 95% CI, 1.20–3.16; p = 0.007, respectively. In the replication study, long-term PPI use was associated with an increased risk of self-reported falling; AOR, 1.51; 95% CI, 1.00–2.27; p = 0.049. No association of long-term PPI therapy with bone structure was observed; however, questionnaire-assessed falls-associated metrics such as limiting outdoor activity (p = 0.002) and indoor activity (p = 0.001) due to fear of falling, dizziness (p < 0.001) and numbness of feet (p = 0.017) and objective clinical measurement such as Timed Up and Go (p = 0.002) and Romberg eyes closed (p = 0.025) tests were all significantly impaired in long-term PPI users. Long-term PPI users were also more likely to have low vitamin B12 levels than non-users (50% versus 21%, p = 0.003). In conclusion, similar to previous studies, we identified an increased fracture risk in subjects on long-term PPI therapy. This increase in fracture risk in elderly women, already at high risk of fracture, appears to be mediated via increased falls risk and falling rather than impaired bone structure and should be carefully considered when prescribing long-term PPI therapy.